Joyce's Non-Fiction Writings "Outside His Jurisfiction" (Springer International Publishing, 2018)
This book presents a fundamental shift in the way we approach, discuss, and evaluate Joyce's non-fictional writings. Rather than simply proposing or applying new methodologies, it historicises and reconceives the critical assumptions that have shaped scholarly approaches to these works for over half a decade, showing that non-fiction as a categorical distinction, no matter how sensible it appears, crumbles under closer inspection. Bringing into conversation a group of key Joyce scholars, this volume acts not only as a vital reimagining of our critical relationship to Joyce's non-fiction, but as a contribution to similar debates being carried out across the broad range of modernist studies.